Diseño del Modelo de Gestión del Mantenimiento para la planta de extrusión Arkiplast Internacional S.A. - Méndez-Rojas, José Daniel (Instituto Tecnológico de Costa Rica, 2018)
Plant Arkiplast internacional S.A., recently enjoys the benefit be functioning in the form of free zone, this expands your demand both domestically and internationally, for this reason it is fundamental to having a high degree of effectiveness, quality and continuous improvement of all processes and their control, which demonstrates the need for a maintenance management model and strategies appropriate to the plant for the achievement of business objectives and be competent at the global level. The project consists in the creation of a maintenance management model and the establishment of strategies that allow the standardization as well as improvement of processes and current maintenance, this unit yields way demonstrate their integration into the production process and how that may impact on the scope of the business objectives. As part of the model establishes a logical tree of productive equipment, coding methodology and analysis of criticality for each of these for what a reliability analysis is carried out with reference to the standard SAE JA-1011 for each of the critical equipment to what you create interdisciplinary working group and the creation of preventive maintenance plans and predictive for each of these back to the delimitation of the border for each of these standard ISO 14224 Improvements to control areas and wineries are established. Establishes the methodology for the incorporation of a computational tool to optimize the process of maintenance promoting intelligent maintenance and improve communication between users and maintainers of equipment. A Balanced Scorecard is defined from the evidenced needs for which action plans and indicators are established with the respective leaders of its follow-up in order to improve controls and performance of the organization to facilitate the establishment of improvements in the process. The proposed improvements are based on the strengthening of the areas with the biggest weakness of the maintenance unit from the application of the audit “MES” and the needs identified on the ground. Finally determines the estimated cost of carrying out preventive work proposed for critical equipment and from two scenarios where there is evidence of the worst and the best with regard to the scope of the proposed targets are evident the benefits expected to implement these tasks in the production process.
Proyecto de Graduación (Licenciatura en Mantenimiento Industrial) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electromecánica, 2018
Keywords: Mejoramiento; Calidad; Eficiencia; Control; Gestión; Mantenimiento; Análisis; Confiabilidad; Comunicación; Cuadro de Mando Integral; Prevención; Research Subject Categories::TECHNOLOGY::Engineering mechanics